Structure of solid lipid nanoparticles produced by a microwave-assisted microemulsion technique. Issue 43 (14th April 2016) - Shah, Rohan M.; Bryant, Gary; Taylor, Matthew; Eldridge, Daniel S.; Palombo, Enzo A.; Harding, Ian H.
Abstract : The current study investigates the structure of solid lipid nanoparticles, prepared using a recently reported microwave-assisted microemulsion technique, by multi-angle static and dynamic light scattering and small angle X-ray scattering techniques. Abstract : We have recently reported a novel microwave-assisted microemulsion technique for the production of solid lipid nanoparticles (SLNs). SLNs are colloidal carriers made from physiologically well-tolerated lipids that are normally solid at room and body temperature. These microwave-produced SLNs have small size, moderate zeta potential, high encapsulation efficiency and low crystallinity. The drug release studies conducted on drug-loaded SLNs are consistent with a core–shell structure for the microwave-produced SLNs, but with significantly different release profiles depending on the drug used. We further employed multi-angle static and dynamic light scattering (SLS/DLS) and small angle X-ray scattering (SAXS) techniques to help elucidate the structure of microwave-produced SLNs. The SLS/DLS data for the SLNs prepared in this study are consistent with a core–shell structure with a shell thickness of ∼13 nm. SAXS data suggest that the SLNs have a lipid lamellar structure with a repeat spacing of 41.0 ± 0.1 Å.